Tajikistan's Difficult Development Path - Olcott, Martha Brill (Book collections on Project MUSE., 2012)
Tajikistan teeters on the brink of failure. This mountainous and landlocked country, the poorest in Central Asia, confronts the challenges of good governance and economic survival. These domestic struggles become even more problematic as international forces prepare to withdraw from neighboring Afghanistan, leaving Central Asian countries to ensure regional stability. In Tajikistan's Difficult Development Path, Martha Brill Olcott traces the political, economic, and social change following the country's independence and international efforts to avert state collapse. The Tajik government's comm.